The green ember - Smith, S. D. (Sam Smith) (Smith, S. D. (Sam Smith). Green ember (Series) ;, 2015)
"Heather and Picket are extraordinary rabbits with ordinary lives until calamitous events overtake them, spilling them into a cauldron of misadventures. They discover that their own story is bound up in the tumult threatening to overwhelm the wider world. Kings fall and kingdoms totter. Tyrants ascend and terrors threaten. Betrayal beckons, and loyalty is a broken road with peril around every bend. Where will Heather and Picket land? How will they make their stand?"--Back cover.